The iconographical diversity of theSirens’ physical forms in medieval bestiaries - Juliana Santos Dinoá Medeiros (Anastasis: Research in Medieval Culture and Art, 2021)
This article analyses the physical representation's forms of the Siren in medieval bestiaries. Depending on the manuscript, the creature could appear in three hybrid forms: bird-woman, fish-woman and fish-bird-woman. The difference draws attention, considering that the text is the same in each manuscript and specifies the Siren's physical as being that of a bird-woman. Starting from a reconstruction of the Siren myth, since its origin to the Middle Ages, we see how the beast was transformed from a bird-woman into a fish-woman and how this very transformation was received in the bestiaries. Considering the particular relation between image and text in bestiaries and conceiving them as independent traditions, we realize that, contrary to previous studies, the distinct representations were not the result of confusion among different creatures. It is the illuminator who associates the textual description (that determined the Siren asa bird-woman) with his contemporary imagery (that consolidated the Siren as a fish-woman).